AGE-FRIENDLY BOSTON'S INCLUSIONARY APPROACH TO IMPLEMENTING ACTION. (11th November 2018) - Coyle, C E; Mutchler, J E; Shea, E; Burns, A
Abstract: The Age-Friendly Boston Initiative, currently in its third year, is implementing and evaluating a 75-item action plan, including efforts to create more dementia-friendly spaces and practices and outreach to socially isolated segments of the community. The Age-Friendly Boston Initiative has worked hard to engage not only older Boston residents, but also non-profit and business partners throughout the City to ensure that residents of all backgrounds and abilities are represented in the initiative. Further, Boston has knit both Age-Friendly and Dementia-Friendly practices together under a single Age-friendly Boston action plan, an approach which supports the coordination of the work and the messaging. This presentation will provide an overview of the full 5-year project, with particular focus on the steps taken to engage the local community and embed these inclusionary practices throughout municipal departments. Results include the progress of action to-date and the development of metrics by which impact can be assessed.